(untitled) (Research, Society and Development, 2021)
This study aimed to investigate the trends of available national contributions on social skills in scientific journals indexed in the area of psychology. This is a narrative review of the scientific literature on the field of social skills in Brazil carried out in the Index Psi database. We have observed 36 articles that met the selection criteria established. Among the main results, we highlight that a prevalent publications profile was presented with children and adolescents as the main target audience, and the Del Prette Social Skills Inventory as an instrument for data collection. We highlight interventions to appropriate the repertoire of social skills in all stages of human development since childhood, with special care for the male sex. It is concluded that the reasonable amount of articles on social skills, are directed to approaches already traditional in the literature with strong influence in the field of psychological and educational studies in general. The panorama evidenced in the present study suggests opening up on the horizon an extensive and important agenda for a better understanding of social skills in the Brazilian scenario, in relation to its association with topics still little investigated, namely, health promotion in the territory, professional categories, lifestyle and quality of life related to health, and the still emerging themes of spirituality and religiosity.